Magnetic Nanoparticles in Human Cervical Skin - Murros, Kari; Wasiljeff, Joonas; Macías-Sánchez, Elena; Faivre, Damien; Soinne, Lauri; Valtonen, Jussi; Pohja, Marjatta; Saari, Pekka; Pesonen, Lauri J.; Salminen, Johanna M. (Frontiers in Medicine, 2019)
Magnetic iron oxide nanoparticles, magnetite/maghemite, have been identified in human tissues, including the brain, heart, liver, and spleen. As these nanoparticles may play a role in the pathogenesis of neurodegenerative diseases, a pilot study explored the occurrence of these particles in the cervical (neck) skin of ten patients with Parkinson’s disease and ten healthy controls. Magnetometry and transmission electron microscopy analyses revealed magnetite/maghemite nanoparticles in the skin samples of every study participant. Regarding magnetite/maghemite concentrations of the single-domain particles, no significant between-group difference was emerged. In low-temperature magnetic measurement, a magnetic anomaly at ~50 K was evident mainly in the dermal samples of the Parkinson group. This anomaly was larger than the effect related to the magnetic ordering of molecular oxygen. The temperature range of the anomaly, and the size-range of magnetite/maghemite, both refute the idea of magnetic ordering of any iron phase other than magnetite. We propose that the explanation for the finding is interaction between clusters of superparamagnetic and single-domain-sized nanoparticles. The source and significance of these particles remains speculative.